2011
DOI: 10.4236/ojsst.2011.13008
|View full text |Cite
|
Sign up to set email alerts
|

Total Ergonomics and Its Impact in Musculoskeletal Disorders and Quality of Work Life and Productivity

Abstract: Studies have indicated the application of ergonomics in improving the quality of work life, reducing musculoskeletal disorders and increasing productivity. On the other hand, there are large differences between developing and developed countries in applying ergonomics knowledge, the need of applying the science of culture, especially in developing countries and the third world is vital, but the culture implementation and pay evaluation of total ergonomics (micro and macro) is low. Therefore, this study has tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
2
Order By: Relevance
“…[8] There were no significant differences found in the control group. These negligible findings may be due to several factors such as how training alone did not improve productivity.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…[8] There were no significant differences found in the control group. These negligible findings may be due to several factors such as how training alone did not improve productivity.…”
Section: Discussionmentioning
confidence: 75%
“…[5] Several research studies have shown that the application of ergonomic principles and programmes in almost all workplaces results in an increase in productivity and, in fact, decreases WMSDs. [6][7][8] Prior investigations conducted on the effectiveness of office ergonomic training reported improvements in knowledge and workstation habits reduced the incidence of MSDs. [9] One particular study used various educational interventions that included posters, emails, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A concretização e a aplicação dos princípios ergonômicos que vislumbrem a identificação e a modificação das inadequações posturais fazem-se necessárias, sendo uma maneira eficaz de se garantir a salubridade, a segurança, o alto desempenho, a motivação e a satisfação na prática odontológica. Em adição, novos modelos de saúde e de segurança do trabalho surgem para exigir dos profissionais um novo reposicionamento, com a introdução e o aprimoramento dos conhecimentos e das aplicabilidades ergonômicas, sobretudo nas universidades, enquanto instituições responsáveis pela formação dos futuros profissionais 19,26,27 . A falta de um planejamento adequado do ambiente e do equipamento de trabalho favorece o surgimento de distúrbios no sistema osteomuscular principalmente nas regiões do pescoço, dos ombros, da parte superior e inferior das costas 23 .…”
Section: Discussionunclassified
“…Pengetahuan tentang makro dan mikroergonomi dapat berpengaruh terhadap peningkatan kualitas hidup dan penurunan MSDs dengan nilai confidence interval atau CI 99% antara kelompok sampel dan kelompok kontrol. 15 Penimbangan merupakan bagian pertama dari proses kerja jasa laundry. Sikap kerja angkat dan frekuensi angkut tidak berhubungan dengan keluhan MSDs karena pekerja pada bagian penimbangan melakukan sikap angkat dalam waktu yang singkat dan sering berpindahpindah ke bagian lain.…”
Section: Pembahasanunclassified